KEBIJAKAN HAMBATAN NON TARIF DI PASAR UNI EROPA TERHADAP EKSPOR KOMODITAS UDANG INDONESIA - Melisa Sunorita; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research purpose is to explain about the trade policy of the European Union towards Indonesia’s shrimp export commodities in the form of non tariff barriers. This research purpose too for explain about Indonesian shrimp harmful to health of European consumers. Unit analysis of this research is a group (the European Unions). This research analysed used neo mercantilisme perspective, protectionisme theory to approve the trade policy of European Union towards Indonesia. This research is a qualitative of research. Data collection method of this research is library research. The result of this research are the existence protection high levels by European Union of European Consumers. The European Commission issued a policy related to food safety and quality standards.Keywords: European Unions, Trade Policy, Non Tariff Barriers, Shrimp and Protectionisme